In Vitro Maturation and In Vivo Integration and Function of an Engineered Cell-Seeded Disc-like Angle Ply Structure (DAPS) for Total Disc Arthroplasty. Issue 1 (December 2017) - Martin, J.; Gullbrand, S.; Kim, D.; Ikuta, K.; Pfeifer, C.; Ashinsky, B.; Smith, L.; Elliott, D.; Smith, H.; Mauck, R.
Abstract Total disc replacement with an engineered substitute is a promising avenue for treating advanced intervertebral disc disease. Toward this goal, we developed cell-seeded disc-like angle ply structures (DAPS) and showed throughin vitro studies that these constructs mature to match native disc composition, structure, and function with long-term culture. We then evaluated DAPS performance in anin vivo rat model of total disc replacement; over 5 weeksin vivo, DAPS maintained their structure, prevented intervertebral bony fusion, and matched native disc mechanical function at physiologic loadsin situ . However, DAPS rapidly lost proteoglycan post-implantation and did not integrate into adjacent vertebrae. To address this, we modified the design to include polymer endplates to interface the DAPS with adjacent vertebrae, and showed that this modification mitigatedin vivo proteoglycan loss while maintaining mechanical function and promoting integration. Together, these data demonstrate that cell-seeded engineered discs can replicate many characteristics of the native disc and are a viable option for total disc arthroplasty.